Exogenous Isolation of Antibiotic Resistance Plasmids from Piggery Manure Slurries Reveals a High Prevalence and Diversity of IncQ-Like Plasmids - Smalla, Kornelia (American Society for Microbiology, 2000)
Antibiotic resistance plasmids were exogenously isolated in biparental matings with piggery manure bacteria as plasmid donors in Escherichia coli CV601 and Pseudomonas putida UWC1 recipients. Surprisingly, IncQ-like plasmids were detected by dot blot hybridization with an IncQ oriV probe in several P. putida UWC1 transconjugants. The capture of IncQ-like plasmids in biparental matings indicates not only their high prevalence in manure slurries but also the presence of efficiently mobilizing plasmids. In order to elucidate unusual hybridization data (weak or no hybridization with IncQ repB or IncQ oriT probes) four IncQ-like plasmids (pIE1107, pIE1115, pIE1120, and pIE1130), each representing a different EcoRV restriction pattern, were selected for a more thorough plasmid characterization after transfer into E. coli K-12 strain DH5α by transformation. The characterization of the IncQ-like plasmids revealed an astonishingly high diversity with regard to phenotypic and genotypic properties. Four different multiple antibiotic resistance patterns were found to be conferred by the IncQ-like plasmids. The plasmids could be mobilized by the RP4 derivative pTH10 into Acinetobacter sp., Ralstonia eutropha, Agrobacterium tumefaciens, and P. putida, but they showed diverse patterns of stability under nonselective growth conditions in different host backgrounds. Incompatibility testing and PCR analysis clearly revealed at least two different types of IncQ-like plasmids. PCR amplification of total DNA extracted directly from different manure samples and other environments indicated the prevalence of both types of IncQ plasmids in manure, sewage, and farm soil. These findings suggest that IncQ plasmids play an important role in disseminating antibiotic resistance genes.